Trends in the Study of Motivation in Schizophrenia: A Bibliometric Analysis of Six Decades of Research (1956–2017) - Najas-Garcia, Antonia; Carmona, Viviana R.; Gómez-Benito, Juana (Frontiers in Psychology, 2018)
Motivation in schizophrenia has been a key research aim for several decades. Motivation is a very complex process underlying negative symptoms that has been assessed and identified using very different instruments and terminologies. This study provides a comprehensive overview of the growing literature production and highlights an extensive set of variables to better understand the study of motivation. Electronic databases were searched in order to compile relevant studies of motivation in individuals with schizophrenia. The initial search identified 3,248 potentially interesting records, and of these, 161 articles published between 1956 and 2017 were finally included. Information such as year of publication, journal, country, and number of authors was codified. Variables related to sample characteristics, methodological aspects, and motivational terms were also extracted. The results revealed a significant growth trend in literature production, especially since the 2000s, with reward as the main term studied. In addition, questionnaires were identified as the preferred instrument to assess motivation in patients with schizophrenia. Other aspects such as country of publication, authors, journals of publication, and co-citation network analysis were also examined. The discussion offers recommendations for future research.